Virtual reality for the promotion of interoception awareness and body image in breast cancer survivors: a study protocol - Sebri, Valeria; Durosini, Ilaria; Strika, Milija; Pizzoli, Silvia Francesca Maria; Mazzocco, Ketti; Pravettoni, Gabriella (Frontiers in Psychology, 2023)
Women who received a diagnosis of breast cancer often report impairments in physical and psychological well-being, even some years after treatments. Individual awareness about physical changes, body image, and current sensations related to their body is important in order to maintain a psycho-emotional balance. Virtual Reality, as an advanced human-computer interface, can be an effective tool to improve breast cancer survivors’ abilities know and manage their current sensations related to their body. The present study protocol proposes a Virtual Reality intervention aiming at promoting interoception and emotional well-being, fear of cancer recurrence, and body perception in breast cancer survivors, according to the three data collection times. Repeated-Measure Analysis of Variance (ANOVA) with between-within interaction will be performed. Expected results include participants’ awareness of their internal feelings, the reduction of negative emotions, and the management of symptoms related to the body, clarifying characteristics for the effective implementation of VR psychological intervention in the future.